2023
DOI: 10.3390/en16031404
|View full text |Cite
|
Sign up to set email alerts
|

Load Forecasting Models in Smart Grid Using Smart Meter Information: A Review

Abstract: The smart grid concept is introduced to accelerate the operational efficiency and enhance the reliability and sustainability of power supply by operating in self-control mode to find and resolve the problems developed in time. In smart grid, the use of digital technology facilitates the grid with an enhanced data transportation facility using smart sensors known as smart meters. Using these smart meters, various operational functionalities of smart grid can be enhanced, such as generation scheduling, real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 195 publications
0
23
0
Order By: Relevance
“…In the proposed model architecture, a 1D-CNN is employed to extract features from the historical load dataset, where the number of filters and kernel size are crucial parameters. Various experiments were conducted with different numbers of filters (32,64,128) and different kernel sizes (3,5,7). It was observed that 128 filters with a window size of 3 generate the lowest validation loss.…”
Section: Model Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…In the proposed model architecture, a 1D-CNN is employed to extract features from the historical load dataset, where the number of filters and kernel size are crucial parameters. Various experiments were conducted with different numbers of filters (32,64,128) and different kernel sizes (3,5,7). It was observed that 128 filters with a window size of 3 generate the lowest validation loss.…”
Section: Model Architecturementioning
confidence: 99%
“…Load forecasting (LF) is a critical component of power system management due to the unpredictable and inconsistent nature of load demand [2]. LF aims to predict future load demands based on current and historical data [3]. LF is commonly classified into three distinct types.…”
Section: Introductionmentioning
confidence: 99%
“…where z W and z U are the weight metrices of the update gate and z b is the bias of the update gate. Next, GRU obtains candidate hidden states through the reset gate based on the updating mechanism of RNN [34], as shown in Equation (3). It can be seen from Figure 1 that the GRU network calculates the combination degree of the current input and the previous status information by the reset gate r t .…”
Section: Bigru Neural Networkmentioning
confidence: 99%
“…where W z and U z are the weight metrices of the update gate and b z is the bias of the update gate. Next, GRU obtains candidate hidden states through the reset gate based on the updating mechanism of RNN [34], as shown in Equation (3).…”
Section: Bigru Neural Networkmentioning
confidence: 99%
“…Similar works such as Wijaya et al (2015), Hsiao (2014), andTaieb (2016) present methods to forecast and analyze consumption drivers based on smart meter data. Dewangan et al (2023) present a recent review on load forecasting models. They focus on smart meter data in smart grids.…”
Section: Introductionmentioning
confidence: 99%